2018
DOI: 10.1149/2.0551810jes
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium Electrowinning in the KF-KBF4-B2O3-KReO4Melt

Abstract: The rhenium electrodeposition from the KF-KBF 4 -B 2 O 3 -KReO 4 melts at 773 K was studied by the cyclic voltammetry. Two waves were found on the E(i) dependences in the cathode region corresponding to the reduction of Re (VII) to metallic Re: Re 7+ +3e→Re 4+ , and Re 4+ +4e→Re 0 . The galvanostatic electrolysis in the KF-KBF 4 -B 2 O 3 -KReO 4 melt in an atmosphere of an ambient air was performed. It was revealed that the use of the KF-KBF 4 -B 2 O 3 -KReO 4 electrolyte (with 5.4 wt% Re) provides the Re elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…KF-KBF 4 -B 2 O 3 -KReO 4 melts are prospective salts for use in rhenium electrolytic reduction [21,22]. The possibility of obtaining compacted rhenium from KF-KBF 4 -B 2 O 3 -KReO 4 melts in the area of the quasi-binary K 2 B 2 OF 6 -KReO 4 melt, particularly under an air atmosphere, was demonstrated in [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KF-KBF 4 -B 2 O 3 -KReO 4 melts are prospective salts for use in rhenium electrolytic reduction [21,22]. The possibility of obtaining compacted rhenium from KF-KBF 4 -B 2 O 3 -KReO 4 melts in the area of the quasi-binary K 2 B 2 OF 6 -KReO 4 melt, particularly under an air atmosphere, was demonstrated in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…KF-KBF 4 -B 2 O 3 -KReO 4 melts are prospective salts for use in rhenium electrolytic reduction [21,22]. The possibility of obtaining compacted rhenium from KF-KBF 4 -B 2 O 3 -KReO 4 melts in the area of the quasi-binary K 2 B 2 OF 6 -KReO 4 melt, particularly under an air atmosphere, was demonstrated in [21,22]. It was found that the electrolysis of KF-KBF 4 -B 2 O 3 -KReO 4 melts can be executed in an open atmosphere at temperatures up to 773 K [21].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the problems of metallurgical processing when working with refractory metals, the electrochemical deposition of compact iridium and rhenium layers, as well as alloys based on them from molten electrolytes, is widely promoted in the scientific literature. The results of these studies have shown that variation of the electrolyte composition [8][9][10][11], temperature [9][10][11][12][13][14] and current density [8,[10][11][12][13] makes it possible to obtain metallic coatings with a controlled structure, chemical and phase composition [10,[12][13][14][15][16][17], including seamless multilayer products (Ir-Re-Ir) of a desired shape [6,9]. As a rule, the electrolytic formation of products composed of refractory metals is carried out in refining baths, when a soluble anode is the source of the working metal.…”
Section: Introductionmentioning
confidence: 99%
“…Melts containing alkali metal fluoroborates and boron oxide are thermally stable, water-soluble, and less aggressive than fluoride melts; they have a low melting point and ability to dissolve metal oxides. [18][19][20] That is why the KF-KBF 4 -B 2 O 3 -KReO 4 melt is a perspective electrolyte for rhenium electrodeposition.…”
mentioning
confidence: 99%
“…In the previous work, 18 we studied the mechanism of rhenium electroreduction on the rhenium substrate in the fluoroborate melt containing potassium perrenate and obtained the compact rhenium layers of the 99.98 wt% purity. The present work is aimed at the study of the initial stages of rhenium electrocrystallization from the KF-KBF 4 -B 2 O 3 -KReO 4 melt on the glassy carbon.…”
mentioning
confidence: 99%